2018
DOI: 10.1002/vjch.201800040
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constitutents from fruits of Macaranga denticulata (Euphorbiaceae) (Part 2)

Abstract: Macaranga denticulata is a 15‐18 m tall plant with rounded edges and long, rounded bark, 5 mm wide black covered with glands. In traditional medicine, this plant was used to treat fulminant hepatitis, dysentery, and urinary retention. In previous studies, we reported 13 isolated compounds from the fruits of Macaranga denticulata. This work presented the isolation and structural characterizations of seven compounds: 5‐((E)‐3,5‐dihydroxystyryl)‐3‐((E)‐3,7‐dimethylocta‐2,6‐dien‐1‐yl)benzen‐1,2‐diol (1), poilaneic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…43 Previous reports identify Macaranga species as rich sources of prenylated flavonoids and stilbenes, many of which have biological activities (including antibacterial properties) that encompasses almost the entire area of pharmacological sciences. 14,27 Marked antibacterial activity of all plant extracts recorded towards S. aureus (ATCC25923, MRSA3 and MRSA6) was in conformity with similar research carried out by Putri and collaborators which showed strong inhibitory activity against S. aureus. 44 The low minimum inhibitory concentration (MIC) and minimum bacteriostatic concentration (MBC) values against Gram-positive bacterial strains exhibited by all plant crude extracts might be owing to their high concentrations in prenylated phenolic contents.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…43 Previous reports identify Macaranga species as rich sources of prenylated flavonoids and stilbenes, many of which have biological activities (including antibacterial properties) that encompasses almost the entire area of pharmacological sciences. 14,27 Marked antibacterial activity of all plant extracts recorded towards S. aureus (ATCC25923, MRSA3 and MRSA6) was in conformity with similar research carried out by Putri and collaborators which showed strong inhibitory activity against S. aureus. 44 The low minimum inhibitory concentration (MIC) and minimum bacteriostatic concentration (MBC) values against Gram-positive bacterial strains exhibited by all plant crude extracts might be owing to their high concentrations in prenylated phenolic contents.…”
Section: Discussionsupporting
confidence: 85%
“…26 Phytochemical studies indicated prenylated flavonoids and stilbenes as the main secondary metabolites found in the genus. 14,27 Other phytochemicals including diterpenes and tannins were also reported from the genus, although few (< 10%) of the 300 species in the genus have been investigated phytochemically. 14 Despite the wide-range of ethnomedicinal applications and potential pharmacological activities of Macaranga species reported in the Pharmacognosy Communications, Vol 11, Issue 2, Apr-Jun, 2021 literature, neither the phytochemical studies nor the antimicrobial efficacy of the crude extracts from M. conglomerata, M. kilimandscharica, and M. capensis have been investigated.…”
Section: Introductionmentioning
confidence: 99%